Australia’s Defence Update 2007:Implications for Southeast Asia - Bateman, Sam (2016)
PRIME MINISTER John Howard launched Australia’s National Security: A Defence Update 2007 in Canberra on 5 July 2007. Like its predecessors in 2003 and 2005, this paper is a review of the balance of concepts, capabilities and forces to meet Australia’s strategic challenges and military commitments. The Australian Government has made some major defence decisions recently, and this latest Update seeks to provide the justification for those decisions. It thus has a flavour of what military staff college students refer to as “situating the appreciation”, or others might call “putting the cart before the horse”.